Warm Autoimmune Hemolytic Anemia with Chronic Hepatitis B - Adefri Wahyudi; Fadrian; Rudy Afriant (Talenta Publisher, 2024)
Background: Warm autoimmune hemolytic anemia (wAIHA) is caused by erithrocytes destruction by IgG or IgG plus C3d-mediated autoantibody. Objective: To present a case of warm autoimmune hemolytic anemia (wAIHA) in a patient with chronic hepatitis B infection. Methods: This is a case report that showed a special case. Results: Man, 64 y.o, hospitalized with diagnosis wAIHA and chronic hepatitis B. Diagnosis of wAIHA is built by: severe normocytic normochromic anemia, reticulocytosis 42.29%, increasing lactate dehydrogenase 397 U/L, direct Coombs test (+4), antibody screening IgG (+4). Anothers laboratorium findings: HbsAg (+), albumin 3.5 g/dL, ALT U/L, rapid HIV (-), anti HCV (-). There is no blast found in peripheral blood and bone marrow smear. Patient also diagnosed chronic hepatitis B inactive phase with negative HbeAg, HBV DNA 547 IU/L, normal liver finding in abdominal USG and moderate fibrosis from fibroscan. Washed red cell transfussion was administered, 2 x 125 mg methilprednisolone iv (3 days) tapering off until to 40 mg/day doses. Conclusion: Steroid is first line therapy in wAIHA. When wAIHA is diagnosed, determination of chronic hepatitis B status should confirmed. There is a risk of reactivation of chronic hepatitis B infection so monitoring is needed.